2008
DOI: 10.1371/journal.pone.0003363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjunct Metformin Treatment in Patients with Type-1 Diabetes and Persistent Inadequate Glycaemic Control. A Randomized Study

Abstract: BackgroundDespite intensive insulin treatment, many patients with type-1 diabetes (T1DM) have longstanding inadequate glycaemic control. Metformin is an oral hypoglycaemic agent that improves insulin action in patients with type-2 diabetes. We investigated the effect of a one-year treatment with metformin versus placebo in patients with T1DM and persistent poor glycaemic control.Methodology/Principal FindingsOne hundred patients with T1DM, preserved hypoglycaemic awareness and HaemoglobinA1c (HbA1c) ≥8.5% duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
114
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(122 citation statements)
references
References 31 publications
5
114
2
1
Order By: Relevance
“…Of the remaining 12 publications, one concerned insulin-requiring type 2 diabetes rather than type 1 diabetes (noted after translation) [61], and one covered a treatment period of fewer than 7 days [62]. Only ten studies were therefore identified [16,17,20,21,23,25,26,[63][64][65]. One of these, which was conducted on participants living in a children's home and did not mention informed consent, was excluded from further analysis [64].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the remaining 12 publications, one concerned insulin-requiring type 2 diabetes rather than type 1 diabetes (noted after translation) [61], and one covered a treatment period of fewer than 7 days [62]. Only ten studies were therefore identified [16,17,20,21,23,25,26,[63][64][65]. One of these, which was conducted on participants living in a children's home and did not mention informed consent, was excluded from further analysis [64].…”
Section: Resultsmentioning
confidence: 99%
“…The final nine studies [16,17,20,21,23,25,26,63,65] covered a total of 192.8 patient years, and the number of completed participants ranged from ten to 92 (median 26) (two studies did not report number completed [17,26]) ( Table 1). The total maximum daily metformin dose varied from 1,000 to 2,550 mg; duration of therapy ranged from 7 days to 12 months (median 4 months).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term effects on offspring of maternal metformin use during pregnancy are unknown. Moreover, there have been concerns regarding an increased propensity to hypoglycaemia in type 1 diabetic patients treated with metformin [2]. Nevertheless, we suggest that there may be a role for metformin in selected obese women with type 1 diabetes in pregnancy.…”
mentioning
confidence: 78%
“…Given the current epidemic of obesity, this is highly relevant because insulin sparing in the treatment of type 1 diabetes may also attenuate weight gain, as shown in several small studies not included in the formal meta-analysis [2].…”
mentioning
confidence: 99%